Implementasi Penegakan Hukum Undang-Undang Nomor 18 Tahun 2014 terhadap Perlindungan Hukum dan Kendalanya pada Orang dengan Gangguan Jiwa di Kota Semarang - Ibadiyah, Annisa Auwla Fil; Listyarini, Dyah; Saputra, Arikha (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The number of people with mental disorders in Semarang City continues to increase. The large number of people with mental disorders in Semarang needs to be addressed seriously to prevent causing discomfort in social activities. Therefore, the author compiled a journal titled "Implementation of Law Enforcement Law Number 18 of 2014 concerning Legal Protection and Constraints on People with Mental Disorders in Semarang City." This journal aims to uncover issues related to how the implementation of Law Number 18 of 2014 on law enforcement against legal protection for people with mental disorders in Semarang City and what factors cause people to experience mental disorders in Semarang City. The research method used in this study is a qualitative method with a socio-legal juridical approach. The data used in this study was obtained using data collection techniques through interviews conducted with Mrs. Lela Dwipayana, S.H. as the Social Rehabilitation Staff of the PMKS Guidance Service Sub-Coordinating Social Welfare Services. The results of this study found that Law Number 18 of 2014 on Mental Health has protected people with mental disorders by being handled by the Social Service in Semarang City.